2006
DOI: 10.1038/nature04751
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a 25-cm asteroid clast in the giant Morokweng impact crater, South Africa

Abstract: Meteorites provide a sample of Solar System bodies and so constrain the types of objects that have collided with Earth over time. Meteorites analysed to date, however, are unlikely to be representative of the entire population and it is also possible that changes in their nature have occurred with time. Large objects are widely believed to be completely melted or vaporized during high-angle impact with the Earth. Consequently, identification of large impactors relies on indirect chemical tracers, notably the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 24 publications
2
52
0
Order By: Relevance
“…The projectile type can, in principle, be identified using the projectile elemental ratios according to the method described in detail by Tagle and Hecht (2006), and by comparing the results to the characteristic element ratios of the different meteorites in a database (Tagle 2004;Tagle and Berlin, Forthcoming). This approach has recently shown to be reliable, as the recent discovery of a projectile fragment in the Morokweng impact melt (Maier et al 2006) confirmed the ordinary chondrite identification previously proposed by McDonald et al (2001), which was based on the analysis of PGE ratios in the impact melt rocks of this crater. The goal of this study is to identify the projectile responsible for the Lappajärvi cratering event using PGE elemental ratios.…”
Section: Introductionmentioning
confidence: 56%
“…The projectile type can, in principle, be identified using the projectile elemental ratios according to the method described in detail by Tagle and Hecht (2006), and by comparing the results to the characteristic element ratios of the different meteorites in a database (Tagle 2004;Tagle and Berlin, Forthcoming). This approach has recently shown to be reliable, as the recent discovery of a projectile fragment in the Morokweng impact melt (Maier et al 2006) confirmed the ordinary chondrite identification previously proposed by McDonald et al (2001), which was based on the analysis of PGE ratios in the impact melt rocks of this crater. The goal of this study is to identify the projectile responsible for the Lappajärvi cratering event using PGE elemental ratios.…”
Section: Introductionmentioning
confidence: 56%
“…The fact that the projectile element ratios of these impact craters (work on the identification of several more impact crater projectiles is currently in progress) overlap with certain chondrite types supports the assumption that chondrite element ratios obtained here are not only representative for the composition of meteorite fragments, but also for the composition of larger bodies. Moreover, the recent discovery of a 25 cm projectile fragment, found almost at the bottom of the impact melt sheet of the Morokweng impact structure (Maier et al 2006) and its classification as an ordinary chondrite conclusively supports the suggested projectile type ) and the method presented herein.…”
Section: Projectile Identification In Terrestrial and Lunar Impact Meltsmentioning
confidence: 79%
“…It may be expected, therefore, that a significant amount of material may also survive a planetary-scale impact into water. Moreover, while material interpreted as fragments of the parent meteorite have been recovered from large oceanic impacts such as Eltanin (Kyte 2002), a recent discovery has shown that fragments can also survive impact into a continental basement, as found in the Morokweng crater, South Africa (Maier et al 2006). For our dry impacts, projectile survivability could not be estimated due to the surviving projectile fragments being fused into sandstone grains, preventing uncontaminated projectile extraction.…”
Section: Projectile Survivabilitymentioning
confidence: 99%